"CLASS APPROACH" AND "PROLETARIAN CHARACTER" OF RUSSIAN REVOLUTION OF 1917 - E E Shults (RUDN Journal of Russian History, 2014)
Study of the problem of “class character” of 1917’ revolution and competency of the term “proletarian revolution”. The author considers questions of participation of various social groups in the Russian revolution, draws analogies of social composition of previous revolutions, considers the principle of “proletarian revolution”, as an ideology element for positioning of Bolsheviks and power capture. It is necessary to consider that an age, gender and national factor played much bigger role un Russian revolution than class factor. Revolution in Russia in many respects leaned on young generations which made more than a third of the population of the Russian Empire by 1917. In fight against tsarism separate calculation was based on the non-russian population and national suburbs of the empire. The special role in the Russian revolution was played by the peasantry. Revolution happened in the capital (in two capitals in Russia), the peasantry remained indifferent to revolution while Bolsheviks didn't begin to take away from them the food violently. This period:(summer - fall of 1919) became the time of peak of the Civil war. However return of landowners and their claim for property of the land forced peasants to turn bayonets for revolution and the earth and, eventually, to provide to Bolsheviks a victory in the Civil war.